2017
DOI: 10.1002/hec.3606
|View full text |Cite
|
Sign up to set email alerts
|

In search of a common currency: A comparison of seven EQ-5D-5L value sets

Abstract: The recently published EQ-5D-5L value sets from Canada, England, Japan, Korea, the Netherlands, Spain, and Uruguay are compared with an aim to identify any similarities in preference pattern. We identify some striking similarities for Canada, England, the Netherlands, and Spain in terms of (a) the relative importance of the 5 dimensions; (b) the relative utility decrements across the 5 levels; and (c) the scale length. On the basis of the observed similarities across these 4 Western countries, we develop an am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 12 publications
1
54
0
5
Order By: Relevance
“…New Zealand. It should also be noted that a comparison of value sets across 7 countries, including the UK [33], found them to have similar characteristics, suggesting that the use of the EQ-5D-5L UK value set in this study is unlikely to have influenced the findings.…”
Section: Discussionmentioning
confidence: 68%
“…New Zealand. It should also be noted that a comparison of value sets across 7 countries, including the UK [33], found them to have similar characteristics, suggesting that the use of the EQ-5D-5L UK value set in this study is unlikely to have influenced the findings.…”
Section: Discussionmentioning
confidence: 68%
“…This general problem of mapping studies is due to regression to the mean [36]. Furthermore, this might also be explained by the preference pattern of EQ-5D-5L, where substantial decrements in preference weights occur at severe health states [30]. The conceptual difference between the source and target instruments may be another explanation.…”
Section: Discussionmentioning
confidence: 99%
“…For ease of exposition, the English value set would be emphasised, though results for other countries' value sets were discussed. The scale length differs across countries with the worst health state or the 'pits' (55555) ranges from -0.446 in the Netherlands to -0.025 in Japan [30].…”
Section: Measures Of Variablesmentioning
confidence: 99%
“…Despite these concerns, another paper in this issue (Olsen, Lamu, & Cairns, ) provides some reassurance. In a comparison of value sets for the EQ‐5D‐5L across seven countries, the authors found that the four “Western” countries of Canada, England, the Netherlands, and Spain showed remarkable similarities considering the use of different modelling methods that produced the algorithms.…”
mentioning
confidence: 99%